Appreciating the House: Housing as an Investment - Wasserman, Miriam (Maine Policy Review, 1999)
A house is both a provider of services that its occupants consume and a long-lived asset that can fluctuate in value. Although homes offer both consumption and investment benefits, most prospective homebuyers give priority to a house’s consumption aspects. As Miriam Wasserman points out, for many buying a home represents the fulfillment of a lifelong dream. Homes become the stage for daily routines and major life events; they give families a sense of achievement and the hope of a secure future. However, the problem with buying a house is that you can’t buy a small share of it. A house is an all-or-nothing deal whose value often dwarfs that of any other single investment. As an investment, economists find that housing is less volatile than stocks, but more so than Treasury bills. In this article, Wasserman discusses the ways in which one’s home constitutes both a consumptive good and a long-term, sometimes risky investment. She also explores the future of housing investment, where it may be possible to own residential real estate without facing the same level of risk that homeowners do today.